ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIK SISWA SMA KARTIKA XIX-4 KELAS X IPS DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Fasha Edma Amalia; Eva Dwi Minarti; M. Afrilianto (IKIP Siliwangi, 2023)
This research is a Classroom Action Research (CAR) whose purpose is to examine the improvement of the mathematical understanding ability (KPM) of high school students in class X on a three-variable system of linear equations. This study uses 3 indicators of KPM. The subjects were students of SMA Kartika XIX-4 involving 12 students. The research was carried out in 4 meetings with 2 cycles. Each cycle was carried out for 2 meetings. The data in this study were analyzed using Normalized Gain / N-Gain, the technique used in data collection was using a test instrument in the form of questions given at the pretest and posttest and using a non-test instrument in the form of an attitude scale questionnaire. The conclusion of this study is that the scientific approach shows a change in student learning that is more independent.